2020
DOI: 10.1016/j.avb.2019.101340
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in bullying: Review and implications for intervention

Abstract: Despite increased research on bullying over the past few decades, researchers still have little understanding of how bullying differentially affects racial and ethnic minority and immigrant youth. To facilitate efforts to better evaluate the impact of bullying among racial and ethnic minority youth and improve interventions, we integrated research from multiple disciplines and conducted a systematic search to review relevant cross-cultural research on the prevalence of bullying, risk and protective factors, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 225 publications
3
87
1
2
Order By: Relevance
“…Future research with more diverse adult samples is clearly needed to extend the present findings and because adults from marginalized populations may face an elevated risk of psychological disorders [e.g., (52)] and barriers to mental health treatment (53). For example, given recent research indicating that racial and ethnic minorities [e.g., (54)] are more likely to experience traditional bullying, it stands to reason that they may also be more susceptible to CBV. Although Kowalski et al (55) found no significant differences in CBV between Black and White participants, they did, however, find that cyberbullying was more strongly linked to loneliness among Black compared to White participants.…”
Section: Discussionmentioning
confidence: 87%
“…Future research with more diverse adult samples is clearly needed to extend the present findings and because adults from marginalized populations may face an elevated risk of psychological disorders [e.g., (52)] and barriers to mental health treatment (53). For example, given recent research indicating that racial and ethnic minorities [e.g., (54)] are more likely to experience traditional bullying, it stands to reason that they may also be more susceptible to CBV. Although Kowalski et al (55) found no significant differences in CBV between Black and White participants, they did, however, find that cyberbullying was more strongly linked to loneliness among Black compared to White participants.…”
Section: Discussionmentioning
confidence: 87%
“…In the current study, we examined bias‐based bullying in the context of immigration. Immigrant‐origin youth are likely to experience bias‐based bullying (Stevens, Boer, Titzmann, Cosma, & Walsh, 2020; Xu, Macrynikola, Waseem, & Miranda, 2020). Although there is a growing body of research that examines the frequency and consequences of youth bullying targeting immigrants, our knowledge is limited regarding how bystanders respond when they observe an immigrant youth being bullied.…”
Section: Bystander Intervention To Bullying and Retaliationmentioning
confidence: 99%
“…In addition, Black, White, and mixed-race children in the United States and other countries tend to report higher levels of bullying than children from other racial/ethnic groups (U.S. Department of Education, 2019), although the effect has been found to vary depending on the racial/ethnic composition of the school and other contextual factors (Xu et al, 2020). Guardianship is important not only because it assumes a central role in opportunity theory, but also because bullying expands as guardianship declines (Peguero, 2009).…”
Section: Current Studymentioning
confidence: 99%